1965
DOI: 10.1002/bscb.19650740107
|View full text |Cite
|
Sign up to set email alerts
|

The isomerization products of humulone

Abstract: The substance known as "isohumulone" is in fact a mixture of four components. They were separated by C.C.D. According to a new nomenclature based mainly on the chemically related humulinic acids A,B, C etc. series they are the stereoisomers isohumulone A and B (IV and V) and alloisohumulone A and B (VI and VII).From the reaction with iodine it was deduced earlier (1) that the isomerization mixture of humulone (I) contained not only isomer 11, but also isomer 111. Counter current distribution (C.C.D.) with a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…In the chromatography, humulinones (cohumulinone (5a), n-humulinone (5b), and adhumulinone (5c)) were eluted earlier than iso-α-acids (Figure 2C). In detail, 5a and 5b, which existed as racemic mixtures (4S5R and 4R5S, Figure 3), 15,32,33 were detected as single peaks, and 5c, which existed as two diastereomers due to the additional fixed chiral carbon (2‴S) in the acyl side chain (5c, 5c′, Figure 3), 25,33 was detected as two equal intensity peaks (5c, 5c′) (Figure 2C). Thus, it was confirmed that this analytical method could separate all of the congeners belonging to humulinones, including the diastereomers of adhumulinone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the chromatography, humulinones (cohumulinone (5a), n-humulinone (5b), and adhumulinone (5c)) were eluted earlier than iso-α-acids (Figure 2C). In detail, 5a and 5b, which existed as racemic mixtures (4S5R and 4R5S, Figure 3), 15,32,33 were detected as single peaks, and 5c, which existed as two diastereomers due to the additional fixed chiral carbon (2‴S) in the acyl side chain (5c, 5c′, Figure 3), 25,33 was detected as two equal intensity peaks (5c, 5c′) (Figure 2C). Thus, it was confirmed that this analytical method could separate all of the congeners belonging to humulinones, including the diastereomers of adhumulinone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The alternative (1,2) shift would lead to a y-pyrone structure 14, which has no chance to be decarbonylated.…”
Section: Second O X I D a T I O N S T E P B E F O R E R I N G C L O Smentioning
confidence: 98%
“…Glycols were reacted with acetone or the dimethyl acetal, according to procedures already described [16,17], or via the glycol sulfite and acetone as reported for aldehydes [17]. Some other dioxanes and dioxolanes were synthesized for comparative purposes (f.i.…”
Section: -Methyl-i 2-propanediolmentioning
confidence: 99%